Ocena ekspercka jako trzeci wymiar ewaluacji krajowych czasopism naukowych - Kulczycki, Emanuel; Rozkosz, Ewa A.; Drabek, Aneta (My University, 2016)
The article discusses the peer-review evaluation of the national scientific journals in the Polish research evaluation system. Our study examines all journals (N = 2212) that are indexed on the 2015 Polish Journal Ranking (the so-called „ministerial list”). It is the first edition of the Polish Journal Ranking in which the peer-review evaluation has been implemented. We have analyzed three dimensions of the evaluation (the formal, the bibliometric, and the peer-review one) in each of the three groups of sciences in which the journals are classified. We have found out that the journal evaluation that is based on the peer-review has fundamentally changed the final assessment of the journals in the group of the humanities. The results of the peer-review evaluation in this group are not related to the results of the formal and bibliometric evaluation. In the group of natural sciences and in the group of social sciences, the results of the peer-review evaluation correlate with the results of the formal and bibliometric evaluation. Moreover, the journals citation correlate with the results of the peer-review evaluation in the three groups of sciences: the natural sciences, the social sciences, and the humanities. Our findings show that adding the third dimension to the evaluation of Polish scientific journals, i.e. peer-review, has resulted in significant transformations of the assessment results only for the humanities journals.
Dziękujemy Alicji Bodych i Piotrowi Brzezińskiemu z Index Copernicus International oraz Sebastianowi Fijałkowskiemu z Ośrodka Przetwarzania Informacji za dostarczenie danych źródłowych o spełnianiu przez czasopisma kryteriów ewaluacji. Za lekturę pierwszej wersji tekstu dziękujemy Małgorzacie Gamian-Wilk, Markowi Hołowieckiemu, Przemysławowi Korytkowskiemu oraz Tomaszowi Zarębskiemu.
Keywords: Ministry of Science and Higher Education in Poland; journal rankings; peer-review; science policy; scientometrics; bibliometrics